Numerical investigation of the heat and mass transfer performance of a two-phase closed thermosiphon based on a modified CFD model - Huicong Yao; Chaoyu Yue; Yinfeng Wang; Haijun Chen; Yuezhao Zhu (Case Studies in Thermal Engineering, 2021)
A modified CFD model was developed to investigate the heat and mass transfer performance of a two-phase closed thermosiphon (TPCT). In this model, the phase-change temperature of the working fluid was considered to be dependent on the local pressure. Meanwhile, an auto-adjust and control strategy was established for the condensation mass transfer time relaxation parameter, which could balance the phase-change pressure to the working pressure. The modified phase-change model was verified by experiments and then used to investigate the heat and mass transfer behaviors of the TPCT under different heat flux of 12.31–15.95 kW/m2. The results indicated that the maximum relative errors of wall temperature and working pressure of the TPCT were 0.25–0.48% and 0.14–0.46%, respectively. The wall temperature gradually decreases from the bottom of evaporator to adiabatic section, and then increases from the bottom to the top of the condenser due to the temperature difference between the inlet and outlet of the cooling water. Also, as the heat flux increase, the overall thermal resistance reduces from 0.060 to 0.055 K/W. These results indicate that the proposed model can be used to predict the heat and mass transfer of the TPCT.